2015
DOI: 10.1039/c4sc03392b
|View full text |Cite
|
Sign up to set email alerts
|

Integration of an anti-tumor drug into nanocrystalline assemblies for sustained drug release

Abstract: A bio-inspired approach was used to integrate an anti-tumor drug into nanocrystalline assemblies for sustained drug release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…HCPT and PPMTX were codissolved in acetone, forming a hybrid solution of drug and excipient. When the hybrid solution was injected into deionized water under sonication, a sudden change of solvent environment occurred, inducing the nucleation of HCPT nanocrystallines and the accompanying coprecipitation of PPMTX onto the growing HCPT nanocrystallines [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…HCPT and PPMTX were codissolved in acetone, forming a hybrid solution of drug and excipient. When the hybrid solution was injected into deionized water under sonication, a sudden change of solvent environment occurred, inducing the nucleation of HCPT nanocrystallines and the accompanying coprecipitation of PPMTX onto the growing HCPT nanocrystallines [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its nanocrystalline form, protected by surfactants or polymers, was obtainable in an anti-solvent precipitation process with water as an anti-solvent in previous studies Yang et al, 2015;Zhao et al, 2015). For instance, our recent study showed that a membrane emulsifier-assisted anti-solvent precipitation could be employed for integration of HCPT nanoneedles with a polymer layer to achieve comet-shaped microparticles with the sustained release property (Yang et al, 2015). We emphasize that HCPT has distinct formula at different pH values, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In a standard experimental set-up, the fast mixing of an alkaline HCPT solution (pH ¼ 13) with an acidic MTX-chitosan one (pH ¼ 2.0) in the presence of ultrasound led to coprecipitation of both ingredients. According to our recent study (Yang et al, 2015), we hypothesize that the growth of HCPT nanocrystals was halted as they were encapsulated by the coprecipitation of the MTX-chitosan conjugate ( Figure 1A). The assumption is strongly supported by a zeta-potential value of +21.4 ± 2.1 mV, which demonstrates the interfacial presence of a positively-charged layer of MTX-chitosan conjugates on each nanoneedle.…”
Section: Resultsmentioning
confidence: 99%
“…Significant progress has been made, and many nanoparticle-based multifunctional drug delivery systems have been successfully prepared, which demonstrate a wide range of combined properties such as long circulating [3, 4], targeting [57], imaging [810], pH sensitivity [11, 12], and sustained drug release [9, 13]. …”
Section: Introductionmentioning
confidence: 99%